2018
DOI: 10.1136/jim-2018-000804
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer aggressiveness and age: Impact of p53, BCL-2 and microvessel density

Abstract: Older men are more likely to have advanced prostate cancer at time of their diagnosis, but whether prostate tumors are inherently (biologically) more aggressive with advancing age is uncertain. To address this gap in knowledge, we analyzed data from veterans (n=971) diagnosed with prostate cancer during 1991–1995. Factors included age, detection of prostate cancer by screening, prostate-specific antigen (PSA) level, anatomic stage, and Gleason score. Information on molecular markers obtained from immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Remarkably, we also found that urine GOAT levels were directly correlated to key clinical parameters associated to PCa aggressiveness, such as Gleason score [14], age [27] and PCR [28]. Henceforth, GOAT urine levels could be also used as non-invasive biomarker for the PCa aggressiveness status.…”
Section: Discussionsupporting
confidence: 53%
“…Remarkably, we also found that urine GOAT levels were directly correlated to key clinical parameters associated to PCa aggressiveness, such as Gleason score [14], age [27] and PCR [28]. Henceforth, GOAT urine levels could be also used as non-invasive biomarker for the PCa aggressiveness status.…”
Section: Discussionsupporting
confidence: 53%
“…Older age was consistently associated with a high-risk Decipher score, even in patients with an ISUP grade of 1, 109 reflecting the more aggressive behaviour of prostate tumours in older people. Tumours in older men also have significantly more p53 immuno reactivity (the abnormal protein produced by the mutant TP53 gene is more stable and tends to accumulate in the nucleus, which allows for detection via an immuno histochemical stain) and high micro-vessel density than younger men, 110 again suggesting that tumours are biologically more aggressive in older men. Also, the epithelial-tomesenchymal transition gene expression profile seems to differ notably between ages, 111 with older individuals having a higher downregulation of transcription factors and mesenchymal markers as well as the overexpression of adhesion factors that are associated with a more aggressive and invasive phenotype, independent of Gleason score.…”
Section: Review Age-related Differences In Histologymentioning
confidence: 99%
“…Age is a risk factor for being diagnosed with prostate cancer. Older men tend to be diagnosed with more advanced disease, 47 but AA men tend to be younger compared to men of other races at the time of diagnosis 48 . Also, racial disparities are greatest for low‐grade Gleason 6 disease compared with Gleason 7 to 10 disease, in which AA men are twice as likely to die of prostate cancer compared with non‐AA men 49 .…”
Section: Discussionmentioning
confidence: 99%